Efeito de um programa de comunicação alternativa para a capacitação de mães de crianças com paralisia cerebral não verbal - Manzini, Mariana Gurian (2013)
Communication is an important resource for child development, because through it the children acquire communication skills and relate to people. Children with severe communication disorders require a rehabilitation program directed to the orientation and manipulation of the user and the family. In this context, it is essential the participation of the person responsible for the child within the family context in the process of choose, development and adaptation of the resource, since parents know better wishes, the center of interest and the routine of their children. The partnership between parents and health professionals has the purpose to make the family an active and cooperative member during this process. The objective of this study was to develop, to implement and to evaluate an Individualized Program of Augmentative and Alternative Communication for parents of children with Cerebral Palsy. The research took place in the Family and School Unity at Federal University of São Carlos, located in São Paulo State, Brazil. The study included 3 children with cerebral palsy and their mothers. In this study was it was used ten instruments; 5 of them were constructed specifically for this study: two protocols about Characterization of the participants; one Interview outline with the objective to identify communication skills already used by the child through the report of the mothers; Protocol for analyze the baseline and intervention with objective to describe in details the video of the baseline and intervention, an outline to analyze mothers perceptions about program effectiveness, Motor Function Measure Classification System with the objective to classify children motor function movements in sitting and walking, Brazil Criterion Questionnaire was used to evaluate and categorize the possession of consumer durables and education level of household head and the Protocol for the Selection of the figures in order to select items from children interest reported by mothers, which are related to the theme of self-care, productivity and leisure. In order to verify the effects of the intervention it used Multiple Baseline Design cross subjects including two phases: baseline and intervention. The results were described in three studies. The study I reveals data on the communication skills of children before and after the intervention. The data showed existing communicative skills in children, and a low input repertoire and acquire new skills through the implementation of alternative communication. The study II data revealed Intervention Process, mothers and children before the intervention process lacked a repertoire of meaningful input before the issue of alternative communication. With the intervention, the repertoire of the mothers was significant and there was an excellent performance in using the same communication capabilities as well as an alternative expressive performance by children in communicating their desires through the figures. Study III showed the mothers' perceptions about the relevance of the use of communication resources to get your kids to express themselves in situations of everyday life. Thus, the premise that the deployment of communications capabilities supplementary and/ or alternative through a partnership with mothers of children with cerebral palsy do not favor the expansion of verbal interaction and acquire new communication skills was confirmed. Considering the results presented above, the above research hypothesis was tested and confirmed. Thus, it is expected that future studies can be developed from the perspective of socializing program in clinical and educational context of daily life of children with cerebral palsy nonverbal.